Penerapan mesin pemisah bunga cengkeh pada petani di Desa Bonto Enrekang - Yiyin Klistafani; Nur Wahyuni; Moh. Adnan (DEDIKASI, 2019)
One agricultural commodity that has high economic value is the clove "Eugenia Aromatica". The many benefits obtained from cloves, making clove commodities sell well in the market due to of high demand. Therefore, the amount of clove production must be able to balance the market demand in order to keep price stability stable. However, post-harvest handling of cloves at the farm level is generally conventional. This has caused problems including long working time (ineffective), the risk of clove quality decreases, and causes discomfort to the skin of workers' hands due to friction of the clove flower for long time. Hence, it is necessary to conduct IbM – “Ipteks bagi Masyarakat” (Science and Technology for Communities) activities in utilizing clove flower separator machines for farmers in Bonto Village, Enrekang. The stages of the implementation of the IbM activities were observation to the farmer groups in Bonto Village, procurement of clove flower separators, conducting training to operate the clove separator mechine and counseling how to do mechine maintenance to farmers in Bonto Village. The results obtained from this community service activity are that clove farmers in Bonto village are able to work more effectively and efficiently in the process of separating clove flowers from their stems so that the production of cloves increases with good quality.